THE IMPACT OF GADGETS ON CHILDREN'S DEVELOPMENT: DELAYED SPEECH AND AUTISTIC DISORDERS - Esnazarova Zulfiya Oljabaevna (Journals Park Publishing, 2022)
In recent years, both parents and teachers have been complaining more and more about delays in speech development: children begin to speak later, they speak little and poorly, their speech is poor and primitive. The article is devoted to troubleshoot plausible reasons along with explaining factors of the issues.
Keywords: delayed speech, the impact of children, autistics disorder, cognitive development.